COVID-19 in LAC : High Frequency Phone Surveys - Results Second Wave - Ballon, Paola; Lara Ibarra, Gabriel; Olivieri, Sergio; Rivadeneira, Ana (World Bank, Washington, DC, 2021)
Coronavirus disease 2019 (COVID-19) continues to preoccupy the population in Latin America and Caribbean (LAC), as do the pandemic’s economic ramifications. The willingness and or ability of people to follow the recommendation to stay at home began to noticeably tail off by the beginning of July. A gradual return to work is observed across all countries, although the situation remains less dynamic than before COVID. Among people re-engaged in the labor market, the majority are coming back to their pre-COVID jobs. Food insecurity has receded but continues to be a major issue for many families in the region. COVID has served to exacerbate existing disparities across the region with respect to medical care. Education continued in most cases thanks to distance learning. On most countries, over 90 percent of children were able to participate in distance learning activities during second wave.